2018
DOI: 10.1007/s00266-018-1103-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Emergence Agitation with Ketamine in Rhinoplasty

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 23 publications
4
42
1
1
Order By: Relevance
“…observational study of children, sex was not associated with the occurrence of EA [54]. Conversely, several studies have shown that male sex is associated with EA in adults [3,8,38,41,55,56]. The higher rate of EA in men is explained by lower pain tolerance and a significant association between postoperative pain and male sex [41,57].…”
Section: Sexmentioning
confidence: 95%
See 4 more Smart Citations
“…observational study of children, sex was not associated with the occurrence of EA [54]. Conversely, several studies have shown that male sex is associated with EA in adults [3,8,38,41,55,56]. The higher rate of EA in men is explained by lower pain tolerance and a significant association between postoperative pain and male sex [41,57].…”
Section: Sexmentioning
confidence: 95%
“…EA is reportedly more common in children than in adults [38,45,46]. In a study of children aged 2 -12 years, the incidence of EA was inversely correlated with age [47].…”
Section: Agementioning
confidence: 98%
See 3 more Smart Citations